Multilingualism in Indonesian Literature: A Literary Review from the Perspective of Anthropolinguistics - Mu'in, Fatchul; Noortyani, Rusma; Sibarani, Robert (TALENTA Publisher, 2021)
There is an interesting problem to raise, namely the use of unique language symptoms in Indonesian literary works. The uniqueness of language use in Indonesian literary works can be seen from two or more languages in Indonesian literary works. The use of two or more languages is called multilingualism in Indonesian literature. Multilingualism in Indonesian literary works is seen as